Creating the female/female creators: Pope, women writers and "The Dunciad". - Kotsovolos, Nastasia. (University of Ottawa (Canada), 1996)
This thesis examines the transformation of gender identity in the early eighteenth century; it demonstrates the ways in which the entry of women into print culture destabilized traditional gender norms; and it demonstrates the effect of such changes upon the life and poetry of Alexander Pope. The first chapter, which is mainly historical, contextualizes women's participation in print culture. It describes how their presence in print signified gender as an artificial or socially constructed category (as opposed to traditional notions of it as absolute and essential). The second chapter surveys various poetry and correspondence of Alexander Pope in order to demonstrate the difficulties and anxieties experienced by Pope as he attempts to deal with fluctuating gender codes of the day. He requires a stable notion of the private feminine Other in order to establish his masculine and public self, yet it is shown that Pope is inexorably linked with the feminine Other from which he endeavours to distance himself; thereby, he unwittingly contributes to the slippage of these terms. The third chapter ties together all the issues discussed in the previous two chapters through a close reading of The Dunciad. Pope's anxiety about gender identity is revealed: he represents his culture, especially literary culture, as having fallen into "feminization" because it has ostensibly rejected masculine values in preference to feminine ones. The reign of Queen Dulness engenders the conditions whereby the body has enslaved the mind, madness has overpowered reason and empty rhetoric has replaced meaningful language. Although Pope attempts to distance himself from all that he represents as corrupt and effeminate in The Dunciad, he is, nevertheless, implicated in the perversion of the very patriarchal systems which he is attempting to uphold. (Abstract shortened by UMI.)
Keywords: Biography.